Benin : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of a Performance Criterion; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report, 2007)
The staff report for the Second Review under the Three-Year Arrangement under the Poverty Reduction and Growth Facility (PRGF) highlights Benin's macroeconomic framework. All quantitative performance criteria (PC) and benchmarks for the period through end-December 2006 were observed, but one structural performance criterion and one structural benchmark were missed. Reform of the civil service pension fund is urgently needed. Benin's newly issued Growth and Poverty Reduction Strategy Paper (GPRSP) places renewed emphasis on private sector-led economic growth.